2022
DOI: 10.5964/jspp.6491
|View full text |Cite
|
Sign up to set email alerts
|

Partisan discrimination without explicit partisan cues

Abstract: Much research has demonstrated that Democrats and Republicans use information about party affiliation to discriminate against one another. However, we know little about how people gain the necessary information about other people’s partisanship to engage in discriminatory behavior. We explore whether people perceive partisanship when shown only images of faces, and whether they then use these perceptions to engage in partisan discrimination. We find that they do. Using two studies we show that the partisan per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The phenomenon also seems tethered to real-world behavior, such as discrimination in college admissions (Iyengar & Westwood, 2015). Lyons and Utych (2022) even found that respondents favored copartisan-looking faces in hiring decisions, as well as interpersonal interactions, in the absence of explicit group labels. This extends to a range of inanimate objects that now carry a cultural sense of party identification (Hiaeshutter-Rice et al, 2021).…”
Section: Affective Polarization and Partisan Violencementioning
confidence: 99%
“…The phenomenon also seems tethered to real-world behavior, such as discrimination in college admissions (Iyengar & Westwood, 2015). Lyons and Utych (2022) even found that respondents favored copartisan-looking faces in hiring decisions, as well as interpersonal interactions, in the absence of explicit group labels. This extends to a range of inanimate objects that now carry a cultural sense of party identification (Hiaeshutter-Rice et al, 2021).…”
Section: Affective Polarization and Partisan Violencementioning
confidence: 99%